Knowledge heterogenization of the franchising literature applying transaction cost economics - Fu-Sheng Tsai; Chin-Chiung Kuo; Julia L. Lin (Economies, 2020)
Transaction Cost Economics is one of the most critical theories for business studies, including Franchise research. Knowing this stream of research well can help researchers to ground and sustain their studies on a more solid theoretical foundation. Through a Scientometric literature review via the Search-AppraisaL-Synthesis-Analysis (SALSA) procedures, this paper proposes, investigates and demonstrates the knowledge heterogenization (i.e., the knowledge structure becoming heterogeneous) of literature in the social science domain. Focused on the Transaction Cost Economics application in Franchising research that intersects Economics and Business areas, knowledge heterogenization is found and demonstrated in the following aspects of research stream development: research topics, targeted outlets, empirical (geographical) contexts, analytic approaches, as well as important scholars and publications. However, we did not find heterogenization in terms of the adoption of cross-sectional versus longitudinal research design and quantitative versus qualitative data sources. Implications for the continuous practices and theory development of this research stream are discussed. Mainly, we argue that knowledge heterogenization is an approach for a scientific community to achieve developmental sustainability.
Keywords: 330; franchising research; knowledge heterogenization; marketing; Scientometrics; transaction cost economics